Factors associated with toddler development - Idris Idris; St Aminah Ali; Desi Eka Pratiwi; Andi Nursiah (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Introduction: Children are the nation's next generation; therefore, they need quality children to achieve a promising future for the country. Growth and development experience a rapid increase at an early age, namely from 0-5 years. Objective: This study knows the factors related to toddler development. Method: The research design uses correlational with a cross-sectional approach. The population of this study was all toddlers, as many as 250 toddlers. The sample of 71 toddlers used the sampling technique of proportionate random sampling. Test data analysis using the chi-square test, continue correction, and alternative Fisher’s exact test. Results: This study showed a significant association between nutritional status (p = 0.04), history of chronic disease (p = 0.01), education (p = 0.04), history of childbirth (p = 0.03), stimulation (p = 0.04) with toddler development and there was no significant relationship between socioeconomic (p = 0.71) and toddler development. Conclusion: there is a relationship between nutritional status, history of chronic disease, education, history of childbirth, and stimulation with toddler development. Health workers should be advised to detect child growth and development early by looking at the history of chronic diseases suffered and stimulating toddlers for optimal development.